Analisis SWOT sebagai Penentu Strategi Persaingan pada Toko Slamet Pasar Pusat Pekanbaru - Suci, Rama Gita; Anggraini , Fauziah Tiara; Sundayu, Niken Nindika; Amelia, Roaina; Azzahra, Sahira (Politeknik Raflesia Press, 2024)
SWOT analysis is useful for evaluating the strengths, weaknesses, and competitive advantages possessed by Toko Slamet with the aim that its business can still run in the midst of such a competitive competition, it must have strategic planning. To find out good planning and strategic, a data obtained by qualitative methods is needed. Based on the results of the study, the conclusion of Toko Slamet's SWOT analysis is that by using the Strength-Threats strategy, it can help Toko Slamet through the threats it is facing.